OSTEOARTHRITIS AND ISCHEMIC HEART DISEASE: THE MODERN ASPECTS OF INFLUENCE AND TREATMENT - Глушко, Л. В.; Федоров, С. В.; Адед, Ізгак (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Pulse, 2019)
Osteoarthritis is the most prevalent form of arthritis, with an associated risk of mobility disability (defined as needing help walking or climbing stairs) for those with affected knees being greater than that due to any other medical condition in people aged 65. The societal burden (both in terms of personal suffering and use of health resources) is expected to increase with the increasing prevalence of obesity and the ageing of the community. Osteoarthritis is a multifactorial process in which mechanical factors have a central role and is characterised by changes in structure and function of the whole joint. The problems of biinfluence of CAD and osteoarthritis, effects of NSAIDs on heart and statins on joints were discussed.